Analisis LKM Posdaya Kenanga Terhadap Tingkat Pendapatan Pelaku Usaha Mikro di Kelurahan Situ Gede - Dalimunthe, Nur Cholilah Junita; Murdianto, Murdianto (Jurnal Penyuluhan, 2015)
LKM is a financial institution that serves to distribute micro-credit to the poor or low-income community. The granted micro-creditis expected to help the community, especially micro entrepreneurs to be able to expand their business. Business development is astrategic step to increase micro entrepreneur revenue. However, LKM should consider about the level of target accuracy, resourceprovivion, and movement development. This research aimed to analyze the implementation of LKM Posdaya Kenanga to microentrepreneur income level in Situ Gede Village. The research methods were The Rank Spearman Test and Cross Tabulationwhich were used to determine the existence of relationship between the implementation of LKM to micro entrepreneur incomelevel. The results showed that the implementation of LKM Posdaya Kenanga did not have positive and significant relationshipto micro entrepreneur level because the amount of micro entrepreneur income was generally low. Keywords: micro credit, micro entrepreneurs, micro enterprises development